The Effect Of Kahoot!-Assisted Interactive Learning On Students' Problem-Solving Abilities In Quadratificial Functions In Grade X - Sormin, David Frendy; Sinaga, Rani; Situmorang, Adi Suarman (Jurnal Pendidikan, Sains Sosial, dan Agama, 2024)
This study aims to determine the effect of interactive learning assisted by kahoot! on the problem-solving ability of class X students in the quadratic function material at the Free Methodist Private High School Medan. This study uses a quasi-experimental method with probability sampling techniques, where class XA is designated as the experimental class and class XB as the control class. The research instrument used is a test. After calculations using the ????- test , the calculated t is 6.474. For α = 0.05 and df = 61-2 = 59 then t_0.05.59 = 2.95 then obtained t_table = 2.95 obtained t_count> t_table, which means reject H_0 and accept H_a. The results of data analysis show that the sig. (2-tailed) value is 0.000 <0.05 at a significance level of 5%, which means there is a significant difference between the experimental and control groups. The average problem-solving score of students in the experimental class was 83.806, while the control class obtained an average of 69.6. The results of the ???? - ???????????????? test showed that the average score of the experimental class was 0.72 (high category), while the control class obtained a score of 0.53 (medium category). The large influence of interactive learning assisted by Kahoot! on students' problem-solving abilities reached 70.1%. Therefore, it can be concluded that interactive learning assisted by Kahoot! has an effect on the problem-solving abilities of class X students of SMA Swasta Free Methodist Medan on the quadratic function material